Factors Determining Quality of Drug Information by Hospital Pharmacies-Results from Five-Year Annual Quality Assessment - Dorothea Strobach; Ute Chiriac; Sigrun Klausner; Sabine Krebs; Claudia Langebrake; Christiane Querbach; Carolin Schuhmacher; Rickmer Schulte; Simon Wiegrebe; Ute Amann (MDPI AG, 2024)
Drug information (DI) provided by hospital pharmacies aims to promote rational and safe drug therapy. While quality assessment for this task is recommended, more knowledge on the factors determining the quality is needed. We aimed to evaluate the impacts of different factors on the quality of DI provided by hospital pharmacies to healthcare professionals. Retrospectively, answers on fictitious enquiries about annual DI tests for German hospital pharmacies over five years were evaluated for content-related and structural requirements. Multivariate analysis was performed for the impact of the enquiry complexity, DI organization (specialized DI center; pharmacist responsible per day; DI on top of other routine tasks), and quality measures (second look; experience of answering pharmacist in DI/on ward; use of documentation database). In 2017-2021, 45, 71, 79, 118, and 122 hospital pharmacies participated. The enquiry complexity had a statistically significant impact on the content-related quality, with poor results for a higher complexity (years 2018/2021, OR 0.25/0.04, p < 0.01). The DI centers achieved better results regarding content-related quality than for a pharmacist responsible per day (OR 0.76/p = 0.65) or DI on top of routine tasks (OR 0.35/p = 0.02). The DI centers scored better in structural quality. The second look showed an overall trend of a better content-related and structural quality. In conclusion, specialized DI centers and second looks are recommended as quality-improving measures. Training for answering complex enquiries should be intensified.